Online searching platforms preferred by students in acquiring information for academic purposes / Lai See May ... [et al.] - May, Lai See; Azmi, Azzieatul Syazwanie; Nizam, Mohamad Farhan; Mohd, Muhammad Fakrul Razi; Muhamad Razali, Mohamad Safwan; Ahmad Tarmizi, Nadia Alisya (2021)
Our life today is inseparable with technologies and information. People utilise the internet to access various information for different purposes like social, entertainment and knowledge. Students nowadays are highly depending on the technology to obtain information especially for academic purposes. Hence, it is crucial for them to determine which websites should they visit to obtain reliable and useful information. This study aims to identify online searching platforms that students prefer to use in conducting literature search for their assignments and to determine the level of students’ awareness on the importance of gaining reliable sources from the worldwide webs for academic purposes. An online survey was conducted among 100 students of various bachelor’s degree programmes from UiTM Cawangan Kelantan. Results showed students prefer using video sharing sites (YouTube, TikTok, SnapChat and etc.), social media sites and microblogs (Facebook, Instagram, Twitter, Pinterest and etc.) over other “traditional” search engines like library online database and Google Scholar to search for various forms of information for the learning. In terms of awareness, majority of the respondents are aware that it is important for them to gain information from reliable resources that are available online by checking the original sources of information and its author credentials prior using and sharing it to others. The respondents also agree that they are rigid when choosing the sources of news and information for their studies. News and information from entertainment blogs and social media sites are certainly not their choice in conducting literature search for academic purposes